Some challenges of our culture to the transmission of the Gospel - Martínez Baigorri, Javier (Razón y fe, 2021)
This article deals with the challenges facing the transmission of the Gospel in today’s world. The point of reference is the evangelization of the group called “young adults”, a group of special interest because it has not yet succumbed to total secularization, and is still searching; and, secondly, because these young people can be considered as a model of today’s post-modern human being. Throughout the article, a journey is made in search of some of the main challenges described in the abundant bibliography that exists on the difficulty of transmitting the Gospel in our day. Since Vatican II, the Church has invited us to update and adapt the way in which we approach the task of transmitting the faith; this is how the term New Evangelization has arisen, a term on which we will reflect.
Keywords: new evangelization; young adults; secularization; faith-culture relationship; young professionals